Perianal sepsis in neutropaenic patients with haematological malignancies: the role of magnetic resonance imaging and surgery. Issue 9 (18th February 2020) - Ashkar, Claudia; Britto, Maneka; Carne, Peter; Cheung, Wa; Mirbagheri, Naseem
Abstract : Perianal sepsis in neutropaenic patients with haematological malignancy is a common and serious complication while presenting many challenges both diagnostically and therapeutically. This retrospective study found that magnetic resonance imaging was able to successfully detect a drainable collection with up to 80% accuracy despite severe neutropaenia. Both conservative and surgical management strategies were safe, lead to resolution of symptoms and few recurrences. Abstract: Background: Perianal sepsis occurs in up to 10% of neutropaenic patients with haematological malignancy and is associated with significant morbidity and mortality. The management of this condition is challenging in neutropaenic patients due to its atypical pathophysiology. The aim of this study is to assess the role of magnetic resonance imaging (MRI) and surgery in neutropaenic patients with perianal sepsis. Methods: A retrospective chart review was performed on all neutropenic patients with a haematological malignancy who had a diagnosis of perianal sepsis during the inpatient admission between 2008 and 2017. Patient characteristics, symptoms, haematological data, MRI result, surgical intervention, intraoperative findings and outcomes including recurrence and mortality were collected. Results: Nineteen neutropaenic patients with haematological malignancy were treated for perianal sepsis, eight (42%) patients were managed conservatively and 11 (58%) were managed surgically. Nine patients underwent MRI, which identified a collection in 88% of cases despite severe neutropaenia. In patients with a collection identified on MRI prior to surgery, 80% had a drainable collection confirmed intraoperatively. Post‐operative complications included two cases of sepsis from a presumed perianal source and one death. A total of 82% of patients experienced symptom resolution after surgery compared to 88% of patients managed conservatively. Conclusion: This study has demonstrated that MRI is a useful diagnostic tool in evaluating perianal sepsis in patients with haematological malignancy, even during periods of severe neutropenia. We found that both conservative and surgical management strategies lead to resolution of symptoms.